(untitled) (Journal of the College of Basic Education, 2023)
The research aims to identify the impact of the Rubin table method on the achievement of fifth grade female students in science. In order to achieve the goal of the research and the hypothesis, the researcher adopted an experimental design located in the field of experimental designs with partial control of the post-test in the achievement of the fifth grade students of the two research groups (experimental and control). The current research community is represented by fifth-grade female students in secondary and preparatory schools for morning girls of the General Directorate of Education of Essaouira for the academic year (2022-2023), and by intentional selection (Anwar Al-Zahraa for Girls) was chosen from among the schools of the current community, and the researcher conducted parity between the students of the two research groups in The following variables: (Achievement scores for the previous academic year in science, previous information test, intelligence test). Verification of its veracity, the level of difficulty of its paragraphs, the strength of their discrimination, the effectiveness of the wrong alternatives to the paragraphs, and the confirmation of its stability by using the half-partition method. The researcher recommended a number of recommendations and proposals that were mentioned in the fourth chapter.